Histopathological Lesions in Gastric and Duodenum Organs in Dogs (Canis familaris) Suspected of Escherichia coli Infection - Olan Rahayu Puji Astuti Nussa; Arya Surya Kuswantos; Lailia Dwi Kusuma Wardhani (The International Journal of Tropical Veterinary and Biomedical Research, 2023)
It is widely known that Escherichia coli (E. coli) can infect the gastrointestinal tract of various animals and damage some tissue organs. Through histopathological examination of the gastric and duodenal organs can provide valuable information relating to how the E. coli infection impacts the animal. On February 6th, 2023, euthanasia and necropsy of a dog belonging to Mr. Kamo Agil were carried out, which is located at Jl. Meyjend Sungkono, Gresik. Anamnesa is known to be a male dog, age ±1.5 months, body weight 0.6 kg. One kennel is filled with 9 dogs, dirty cage, in the house is not unused, damp and close to the warehouse area and furniture office. The dog has never been vaccinated and has not been dewormed. Temporary diagnosis of dogs with colibacillosis. Examination of pathology is carried out macroscopically and microscopically. Microbiological examination with isolation of escherichia coli bacteria and eosin methylene blue agar media. Followed by Gram staining and biochemical tests. The results of anatomical pathology examination showed that the dog had gastroenteritis. The results of microbiological examination showed that isolated and identified escherichia coli from duodenal organs. Based on the results of examinations showed that the dog had gastroenteritis caused by caused by escherichia coli infection.